2020
DOI: 10.1093/narcan/zcaa026
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of mutational signatures of unknown etiology

Abstract: Although not all somatic mutations are cancer drivers, their mutational signatures, i.e. the patterns of genomic alterations at a genome-wide scale, provide insights into past exposure to mutagens, DNA damage and repair processes. Computational deconvolution of somatic mutation patterns and expert curation pan-cancer studies have identified a number of mutational signatures associated with point mutations, dinucleotide substitutions, insertions and deletions, and rearrangements, and have established etiologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…However, the underlying mechanisms that give rise to most mutational signatures in cancers have not definitively been described [ 74 ]. Remarkably, almost one-third of human tumors exhibit mutational patterns of unknown etiology [ 2 ]. It is clear that mutagenesis is dictated by the interaction of specific DNA lesions or endogenous obstacles with error-prone DNA polymerases and repair mechanisms.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the underlying mechanisms that give rise to most mutational signatures in cancers have not definitively been described [ 74 ]. Remarkably, almost one-third of human tumors exhibit mutational patterns of unknown etiology [ 2 ]. It is clear that mutagenesis is dictated by the interaction of specific DNA lesions or endogenous obstacles with error-prone DNA polymerases and repair mechanisms.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, the underlying molecular etiology of mutational patterns in human tumors remains incompletely understood. Despite promising advances, we remain at the early stages of experimental validation of observed mutation patterns [ 1 ]; the mechanism of almost one-third of all cancer mutational signatures is not yet known [ 2 ] while others exhibit complexity that requires further dissection.…”
Section: Introductionmentioning
confidence: 99%
“…The fusion events associated with MSI CRC were much less frequent in other MSI non-CRCs, raising a possibility that mutagenic processes underlying fusions are tissue context specific. 13 , 14 Gut microbiota–related sustained inflammation, in part through production of butyrate and other metabolic products, triggers 8-oxo-G DNA lesions in colon epithelium, which is repaired via BER and MMR (Fig 4 A). 11 , 12 …”
Section: Resultsmentioning
confidence: 99%
“…The fusion events associated with MSI CRC were much less frequent in other MSI non-CRCs, raising a possibility that mutagenic processes underlying fusions are tissue context specific. 13,14 Gut microbiota-related sustained inflammation, in part through production of butyrate and other metabolic products, triggers 8-oxo-G DNA lesions in colon epithelium, which is repaired via BER and MMR (Fig 4A). 11,12 Our cohort did not have microbiome data, but we jointly analyzed microbiome data 6 and estimated proportional weights of the mutational signatures for TCGA CRC samples 15 and found that several microbial taxa, especially certain orders of firmicutes, beta-proteobacteria, cyanobacteria, are enriched in the tumors with dMMR signatures (Figs 4B and 4C; Spearman correlation .…”
Section: Colon-specific Dna Damage and Kf Preferencementioning
confidence: 99%
“…in the liquid biopsy fraction typically carries mutational signatures of smoking and other pollutants ( Abbosh et al, 2017 ). Since a liquid biopsy sample carries an admixture of DNA fragments derived from potential tumor tissues as well as hematopoietic and other non-malignant tissues ( Hu et al, 2020 ), which are present even in healthy individuals, an analysis of the mutational signatures in cfDNA can help identify the presence of nucleic acid contents from unexpected tissue types ( Gerstung et al, 2020 ). In addition, cfDNA fragments in the blood typically are 120−220 bp, or multiples thereof, with a maximum peak at 167 bp − which corresponds to the length of DNA wrapped around a single nucleosome in the source tissue, and therefore the genome-wide landscape of cfDNA fragments provides information about epigenome of the cell of origin.…”
Section: Introductionmentioning
confidence: 99%